Cross-lagged analysis of social support, physical activity behavior, and family relationships among university students - Zhou, Xielin; Zhang, Mu; Li, Bo; Ma, Shasha (Frontiers in Psychology, 2024)
Objective To explore the causal relationship between social support, physical activity behavior, and family relationships among university students. Methods Using the Social Support Rating Scale, the Physical Activity Behavior Self-Assessment Scale, and the Family Relationships Scale, a longitudinal follow-up survey was conducted on 412 college students in Sichuan Province at 2-month intervals in March 2024 (T1) and May 2024 (T2), to analyze the interaction mechanisms between college students' social support, physical activity behaviors, and family relationships through cross-lagging. Results (1) There are significant gender differences in social support, physical activity behavior, and family relationships among college students. Among the cross-lagged paths found, except for the path from T1 social support to T2 family relationships (β: 0.40 > 0.21), all other cross-lagged paths are smaller for female college students compared to male college students; (2) T1 social support was able to positively predict T2 physical activity behaviors (β = 0.50, p < 0.001), and T1 physical activity behavior can also positively predict T2 social support (β = 0.18, p < 0.01), but the path value T1 social support → T2 physical activity behavior is larger than T1 physical activity behavior → T2 social support. Therefore, social support is a causal variable for physical activity behavior; (3) T1 social support positively predicts T2 family relationships (β = 0.26, p < 0.001); (4) T1 family relationships positively predict T2 physical activity behavior (β = 0.30, p < 0.001). (5) Physical activity behavior is a mediating variable between family relationships and social support, with a mediating effect size of 0.054. Conclusion There are gender differences in social support, physical activity behavior, and family relationships among college students; there is a longitudinal causal relationship between social support, physical activity behavior, and family relationships; social support is a causal variable of physical activity behavior, and social support is also a causal variable of family relationships, and family relationships are the Social support is a causal variable for physical activity behavior, social support is also a causal variable for family relations, and family relations are a causal variable for physical activity behavior, which has a partially mediating role in family relations and social support.